Pediculicidal Activity of Cem-ceman White Cempaka Flower (Michelia alba DC.) against Pediculus humanus capitis - Ahmad Fadli Robby; Iman Surya Pratama; Galuh Tresnani (Universitas Islam Negeri Alauddin Makassar, 2021)
The prevalence of pediculosis reported in Asia has ranged from 0.7% to 59%. High resistance and side effects is a challenge in using the pediculicidal agents. The widely use and empirical as well as scientific studies of traditional plants for anti-lice were already done, one of them is cempaka. The aim of this study was to determine the pediculicidal activity of cem-ceman white cempaka flower (Michelia alba DC.) on Pediculus humanus capitis in vitro. The white cempaka flowers made into cem-ceman preparations by mixing and soaking in coconut oil until 3 days. Pediculisidal activity was tested by filter paper diffusion test method with 3 replications. Data were analyzed using Kruskal-Wallis followed by post hoc Mann-Whitney Method test with software SPSS v.16. The phytochemical screening showed that sample contains alkaloid, tannin, saponin, and triterpenoid. Pediculidal activity test showed that cem-ceman white cempaka flower has pediculicidal effect in 10% concentration (w/v) with 66.67% mortality and 15% concentration (w/v) with 77.33% mortality. In conclusion cem-ceman white cempaka flowers has pediculicidal activity at concentration 10% and 15% but lower than permethrin 1% (p<0.05).